The Poincaré series of the module of derivations of some monomial rings - Micale, V. (MATHEMATICA SCANDINAVICA, 2008)
Let R be a quasi-homogeneous k-algebra and M be a finitely generated graded R-module. The formal power series _i_k(tor_i^R(k,M)z^i is called the Poincaré series of M and it is denoted by P_M^R(z). We remark that the Poincaré series of the module of derivations of a monomial ring is rational and determine it in some cases.